Connection of boxers` combat styles with psycho-physiological characteristics - Korobeynikov, G. V.; Aksutin, V. V.; Smoliar, I. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: By dominating physical characteristics boxers` combat styles are divided into "strongmen", "paced in hold" and "players". However, connection of combat style with psycho-physiological characteristics of elite boxers has been remained not determined.